RAR‐Related Orphan Receptor Gamma (ROR‐γ) Mediates Epithelial‐Mesenchymal Transition Of Hepatocytes During Hepatic Fibrosis. Issue 8 (27th April 2017) - Kim, Sung Min; Choi, Jung Eun; Hur, Wonhee; Kim, Jung‐Hee; Hong, Sung Woo; Lee, Eun Byul; Lee, Joon Ho; Li, Tian Zhu; Sung, Pil Soo; Yoon, Seung Kew
ABSTRACT: The epithelial‐mesenchymal transition (EMT) is involved in many different types of cellular behavior, including liver fibrosis. In this report, we studied a novel function of RAR‐related orphan receptor gamma (ROR‐γ) in hepatocyte EMT during liver fibrosis. To induce EMT in vitro, primary hepatocytes and FL83B cells were treated with TGF‐β1. Expression of ROR‐γ was analyzed by Western blot in the fibrotic mouse livers and human livers with cirrhosis. To verify the role of ROR‐γ in hepatocyte EMT, we silenced ROR‐γ in FL83B cells using a lentiviral short hairpin RNA (shRNA) vector. The therapeutic effect of ROR‐γ silencing was investigated in a mouse model of TAA‐induced fibrosis by hydrodynamic injection of plasmids. ROR‐γ expression was elevated in hepatocyte cells treated with TGF‐β1, and ROR‐γ protein levels were elevated in the fibrotic mouse livers and human livers with cirrhosis. Knockdown of ROR‐γ resulted in the attenuation of TGF‐β1‐induced EMT in hepatocytes. Strikingly, ROR‐γ bound to ROR‐specific DNA response elements (ROREs) in the promoter region of TGF‐β type I receptor (Tgfbr1) and Smad2, resulting in the downregulation of Tgfbr1 and Smad2 after silencing of ROR‐γ. Therapeutic delivery of shRNA against ROR‐γ attenuated hepatocyte EMT and ameliorated liver fibrosis in a mouse model of TAA‐induced liver fibrosis. Overall, our results suggest that ROR‐γ regulates TGF‐β‐induced EMT in hepatocytes during liver fibrosis. We suggest that ROR‐γ may become a potential therapeutic target in treating liver fibrosis. J. Cell. Biochem. 118: 2026–2036, 2017. © 2016 The Authors. Journal of Cellular Biochemistry Published by Wiley Periodicals Inc. Abstract : ROR‐γ regulates hepatocyte EMT via Tgfbr1 and Smad2 trascription. ROR‐γ is upregulated in human cirrhotic livers and fibrosis‐induced mouse livers, and in vivo silencing ROR‐γ attenuated EMT and ameliorated the liver pathology.